2020
DOI: 10.1177/2515127420925015
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Learning at the Boundary: How to Learn From a Local Cheese Maker

Abstract: The learning innovation we report in this article is an international rapid-prototyping event (48 hours) in which teams of international BSc and MSc students from two universities (Western Europe and South-East Africa, respectively) jointly designed and developed a prototype for a local small-business owner in a developing economy. The learning innovation has its origin in the simple observation that the majority of the current theories, cases, and learning activities that characterize entrepreneurship educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Furthermore, this study also showed that the course material was intended to focus on material contained in an epistemological and ontological manner that was oriented towards Elementary School. Lans et al (2020) emphasise that learning innovation originates from the latest learning activities. According to Mayes (2015), certain methods for promoting ideal learning have confirmed their effectiveness in learning achievement.…”
Section: Materials Of Pancasila and Citizenship Education For Element...mentioning
confidence: 99%
“…Furthermore, this study also showed that the course material was intended to focus on material contained in an epistemological and ontological manner that was oriented towards Elementary School. Lans et al (2020) emphasise that learning innovation originates from the latest learning activities. According to Mayes (2015), certain methods for promoting ideal learning have confirmed their effectiveness in learning achievement.…”
Section: Materials Of Pancasila and Citizenship Education For Element...mentioning
confidence: 99%
“…First, offering entrepreneurship education outside the classroom provides increased accessibility. For Lans et al (2021, p. 529), “Entrepreneurship education has to go beyond simply channeling students through a western entrepreneurship funnel, paying little attention to the diversity”. Offering entrepreneurship education outside the classroom is increasingly being employed outside business schools to engage with the challenge of real-world wicked problems (Turner & Gianiodis, 2018).…”
Section: Pedagogies Of Boundary Crossing Applied To the Lighthousementioning
confidence: 99%
“…Third, context needs to be valued. There are increasing calls for the situated nature of opportunity and entrepreneurial practices to be recognized (Lans et al, 2021; Welter, 2011; Woods et al, 2022). This requires valuing local and Indigenous knowledge, values, and experiences.…”
Section: Pedagogies Of Boundary Crossing Applied To the Lighthousementioning
confidence: 99%
See 1 more Smart Citation
“…In the information age, the influence of the developing media has been paid ever-more attention by the public. Under the influence of various forms of media, the influence of film is more direct and profound ( Lans et al, 2021 ). The development of film will have a certain impact on people’s way of thinking, behavior, and lifestyle ( Vidmar, 2020 ).…”
Section: Introductionmentioning
confidence: 99%